The Distribution of Clay Minerals and Their Impact on Diagenesis in Glen Torridon, Gale Crater, Mars. Issue 10 (20th October 2022) - Rudolph, A.; Horgan, B.; Johnson, J.; Bennett, K.; Haber, J.; Bell, J. F.; Fox, V.; Jacob, S.; Maurice, S.; Rampe, E.; Rice, M.; Seeger, C.; et al.
Abstract: Glen Torridon (GT) is a recessive‐trough feature on the northwestern slope of "Mt. Sharp" in Gale crater, Mars with the highest Fe‐/Mg‐phyllosilicates abundances detected by the Curiosity rover to date. Understanding the origin of these clay minerals and their relationship with diagenetic processes is critical for reconstructing the nature and habitability of past surface and subsurface environments in Gale crater. We aim to constrain the distribution and extent of diagenesis using compositional and morphological trends observed by visible‐to‐near infrared reflectance spectra in GT from Mastcam and ChemCam, supported by high‐resolution images from the Mars Hand Lens Imager. Spectral features consistent with nontronite and fine‐grained red hematite are ubiquitous throughout lower GT, and are strongest where diagenetic features are limited, suggesting that both were formed early, before burial. Diagenetic features increase in both abundance and diversity farther up‐section, and we observe morphologic evidence for multiple episodes of diagenesis, with the edge of a diagenetic front partially preserved in the middle stratigraphic member, Knockfarril Hill. Near the contact between GT and the overlying Greenheugh pediment capping unit, we observe a lack of clay minerals with signatures consistent instead with coarse‐grained gray hematite, likely formed through late‐diagenetic alteration. We hypothesize that the sandstone‐dominant Stimson formation acted as a conduit for diagenetic fluid flow into the area and that the clay‐rich impermeable GT slowed the flow of those fluids, leading to enhanced alteration surrounding the clay‐rich portions of GT, including within the nearby Vera Rubin ridge. Plain Language Summary: The clay mineral‐rich region of Glen Torridon on Mt. Sharp provides information to reconstruct the past habitability of the ancient lake environment in Gale crater. Clay minerals have a unique structure that allow for organic matter to be preserved, so regions with high concentrations of clay minerals are of interest for planetary exploration. We use data from the Mastcam cameras, Chemistry and Camera instrument, and Mars Hand Lens Imager on the Mars Science Laboratory Curiosity rover to search for trends in rock composition and visual properties to investigate how they have been altered by surface and subsurface water over time. This work has shown that regions with high clay mineral abundances restrict groundwater from penetrating deep into rock units, helping preserve remnants of the early environments where the clay minerals formed, some remnants are exposed on the modern‐day surface. Additionally, we observe textural evidence, supported by inferred compositions from spectral data that multiple water‐rock interactions led to enhanced alteration and destruction of clay‐minerals along the edges of the clay‐rich regions. This suggests that there has been a complex history of water‐rock interactions in Gale crater, but that regions with high abundances of clay‐minerals may still have preserved signs of life. Key Points: Glen Torridon exhibits spectral signatures consistent with Fe‐bearing clay minerals and fine‐grained red hematite within all members The Hutton interval, on the uppermost edge of Glen Torridon, has no clay mineral spectral signatures and instead shows evidence of hematite coarsening Clay minerals and fine‐grained hematite formed via early weathering and oxidation while coarse‐grained hematite formed via late diagenesis